Persistent taxane‐induced neuropathy in elderly patients treated for localized breast cancer - Pabst, Lucile; Velten, Michel; Fischbach, Cathie; Kalish, Michal; Pflumio, Carole; Pivot, Xavier; Petit, Thierry (The breast journal, 2020)
Breast cancer is the most common cancer among women. Localized breast cancer treatments involve taxanes which are often responsible for acute peripheral neuropathy. The persistence of taxane‐induced peripheral neuropathy (TIPN) is scarcely described among elderly women. A monocenter historical cohort study including all women over 65 years of age treated between 2001 and 2016 with a taxane‐based chemotherapy for localized breast cancer was carried out at the Paul Strauss Regional Comprehensive Cancer Center. All cases included were followed up for at least 2 years, deaths from causes unrelated to TIPN were excluded. We report on the frequency and risk factors and establish a prognostic score of persistent Common Terminology Criteria for Adverse Events (CTCAE) grade 2 and 3 TIPN. Among the 302 included patients, 21% and 9% developed persistent TIPN of grade 2 and 3, respectively. Two patients died from complications of grade 3 TIPN. Risk factors of persistent grade 2 and higher neuropathy included age (P < .0001), body mass index (P < .0001), and diabetes (P = .0093). Persistent TIPN was more frequent with paclitaxel than docetaxel (OR = 5.43; P < .0001). Patients presenting all four major risk factors had a 97.2% probability of developing long‐term symptoms against 1.2% for patients showing no risk factor. We therefore identified 3 prognostic groups. TIPN is a frequent and sometimes severe persistent side effect of breast cancer treatment among elderly women with a major impact on health‐related quality of life. Chemotherapy regimens without taxane could therefore be a valid option in elderly patients with neurotoxicity risk factors.